The varieties of OA resistance: a response to Gareth J Johnson. (5th September 2018) - Anderson, Rick
In a recent Insights article, Gareth J Johnson reports on research designed to determine the reasons that so many authors still fail to embrace open access (OA) publishing, despite many years of advocacy on the part of a dedicated community of OA practitioners. To answer this question, Johnson interviewed OA practitioners at 81 UK universities, seeking their insights into the attitudes of academic authors. In response to Johnson's findings, this paper proposes three categories of authorial resistance, questions the effectiveness of asking third parties to interpret the thinking of authors (particularly when those third parties have a vested interest in the authors' adoption of OA) and critiques some of the assumptions underlying the informants' reports (most importantly, the assumption that resistance arises necessarily from misunderstanding or misinformation).